2018
DOI: 10.1039/c8ra07944g
|View full text |Cite
|
Sign up to set email alerts
|

Bamboo leaf-based carbon dots for efficient tumor imaging and therapy

Abstract: In this study, carbon dots synthesized from bamboo leaf cellulose were used simultaneously as a staining agent and for doxorubicin delivery to target cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 34 publications
1
33
0
1
Order By: Relevance
“…They were discovered by Xu et al at the University of South Carolina, during separation of single-walled carbon nanotubes. 1 Because of their properties such as low cost, low toxicity, an adjustable luminescence range, excellent light stability, and absence of photobleaching and light ickering, CDs have a broad range of potential applications, e.g., in optical biomarkers, [2][3][4] drug delivery, 4,5 cancer diagnosis, 6 chemical sensing, [7][8][9][10] catalysis, 11 light-emitting devices, 12 and bioimaging, 13 and have attracted wide research interest.…”
Section: Introductionmentioning
confidence: 99%
“…They were discovered by Xu et al at the University of South Carolina, during separation of single-walled carbon nanotubes. 1 Because of their properties such as low cost, low toxicity, an adjustable luminescence range, excellent light stability, and absence of photobleaching and light ickering, CDs have a broad range of potential applications, e.g., in optical biomarkers, [2][3][4] drug delivery, 4,5 cancer diagnosis, 6 chemical sensing, [7][8][9][10] catalysis, 11 light-emitting devices, 12 and bioimaging, 13 and have attracted wide research interest.…”
Section: Introductionmentioning
confidence: 99%
“…The in vitro confocal microscopy studies demonstrated blue fluorescence as well as cellular pathways, highlighting the folate receptor mediated endocytosis mechanism for reaching Hela cells. The selective uptake of NCDs was confirmed by flow cytometry and cell viability data [[ 97 ]97].…”
Section: Applications Of Ncds In Drug Deliverymentioning
confidence: 95%
“… Types of NCDs Types of drug Applications Reference NCDs for synthetic drugs 1 Daucus carota subsp. Sativus (carrot)NCDs Mitomycin Anticancer [ 15 ] 2 Bamboo leaf cellulose NCDs Doxorubicin Anticancer [ 97 ]97] 3 Nitrogen doped-persimmon fruit NCDs Doxorubicin and Gemcitabine Anticancer [ 103 ] 4 Saffron NCDs Prilocane Local anesthetic [ 104 ] 5 Pasteurized milk NCDs Lisinopril Hypertension and renal diseases [ 105 ] 6 Mulberry leaves (Morus alba L.) Lycorine Anticancer [ 106 ] 7 Radix Puerariae Carbonisata NCDs Baicalin Anticancer, Antiviral [ 71 ] 8 Nitrogen doped chrysanthemum buds NCDs Curcumin [ 107 ] 9 O-carboxymethyl chitosan nanoparticles (OCMC-MMA NPs)CDs Telmisartan Anticancer [ 108 ...…”
Section: Applications Of Ncds In Drug Deliverymentioning
confidence: 99%
“…Fahmi et al . reported the preparation of CDs from bamboo leaves cellulose [57] . For the synthesis of carbon dots, the pyrolysis method was employed followed by dialysis for purification.…”
Section: Synthesis Purification and Functionalization Of Carbon Dotsmentioning
confidence: 99%